Analisis dan Pengembangan Sistem Pencatatan Pelaporan Surveillance Campak - Rajak Hasyim; Hari Basuki Notobroto; Irwan Mustafa (Poltekkes Kemenkes Padang, 2024)
Analysis and evaluation of the measles surveillance system is continuous monitoring in efforts to prevent and control measles cases through recording reporting. The aim was to describe, identify and develop a model for a measles surveillance reporting recording system in North Maluku Province based on a systems approach (input, process and output). This research is a system development that includes actions to create a new system or improve an existing one, carried out at the North Maluku Provincial Health Service from January to February 2024. The research involved the measles surveillance information system unit and informants. Information system development stages include data normalization, grouping data into tables or relationships, and creating Entity Relationship Diagrams. The findings show that in the analysis of problems with the information system for recording measles surveillance reporting, system problems were found in the input, process and output components. This reporting note provides information regarding the measles disease surveillance system, namely in health facilities, laboratories and surveillance units. The measles surveillance program has improved its information system, but faces challenges such as inconsistent patient IDs, duplicative data recording, manual storage, and 70% completeness and accuracy. In conclusion, although the measles surveillance program has experienced improvements in its information system, further efforts are still needed to increase accuracy and efficiency through data automation and standardization of variable recording.